Kegiatan Penguatan Kapasitas Aparatur Pemerintahan Desa dalam Pengelolaan Keuangan di Desa Tua Pejat Kecamatan Sipora Utara, Kabupaten Kepulauan Mentawai - Hendri Koeswara; lham Aldelano Azre; Rozidateno Putri Hanida (Warta Pengabdian Andalas)
Discourse on the concept of strengthening village government is one aspect that is often forgotten in the Village Law regime. Even though the village manages a lot of financial resources that require qualified Human Resources capabilities so that the objectives and demands of the Village Law are achieved. At present, village financial management is regulated through Permendagri No. 20 of 2018 in addition to other regulations issued by the Ministry of Villages and PDTT and the Ministry of Finance. The capacity of Tua Pejat Village Government is considered not yet capable of exercising the authority it has under the Village Law to manage village financial resources. This dedication activity is to increase the knowledge and ability of the Old Pejat Village Government apparatus in financial management. This training implementation method in community service starts from training preparation, planning, budgeting, administration, and reporting. The weak capacity of the village government has an impact on the failure of the implementation of the Village Law so that it leads to poor village development, so that important activities to be carried out so that village financial management in Tua Pejat Village is accountable, participatory, and carried out in an orderly and budgetary discipline.